Effect of increased CO2 on iron‐light‐CO2 co‐limitation of growth in a marine diatom. Issue 1 (18th November 2021) - Ye, Youting; Sunda, William G.; Hong, Haizheng; Shi, Dalin
Abstract: Light affects iron (Fe) growth requirements in marine phytoplankton while CO2 can influence energy allocation and light sensitivity. Therefore, ongoing increases in seawater CO2 concentrations could impact the growth of Fe‐ and light‐limited phytoplankton. In this study, Phaeodactylum tricornutum was used as a model diatom to examine the interactive effects of Fe, light, and CO2 on photosynthesis, growth, and protein expression in marine phytoplankton. Low concentration of biologically available inorganic iron (Fe′) and low‐light intensity decreased specific rates of carbon (C)‐fixation and growth, and the two together had an even greater effect, indicating a co‐limitation. Increased partial pressure of CO2 from its current value (400 μ atm) to 750 μ atm had no effect at growth sufficient levels of Fe and light, but increased C‐fixation and growth rate under Fe or light limitation, and had an even greater effect in Fe and light co‐limited cells. The results suggest that ongoing increases in CO2 may increase C‐fixation rates in Fe‐ and light‐limited and co‐limited regions, which cover at least 30% of the ocean. Measurements of photosynthetic proteins in photosystems II and I, and transcripts of proteins involved in CO2 concentrating mechanisms (CCMs), photorespiration, and antioxidant protection, suggest that the benefit of increased CO2 in the Fe‐ and light‐limited cells was from a downregulation of CCMs and resultant decreased demands for energy supplied from photosynthesis, and from decreased rates of photorespiration, which consumes photosynthetically produced ATP and NADPH. A decrease in oxidative stress with increased CO2 also contributed.